(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The latest trend in the development of combat equipment is the increasing penetration of automated and automatic systems with a variety of purposes. In its bigger part, these systems include electrical machines, electrohydraulic, electronic and gyroscopic units and assemblies. The considerable complexity of the electro-automation of machinery, even with high reliability, leads to an increase in the probability of the occurrence of failures and the need to increase the requirements for the qualification of the engineering staff of the repair staff. The study of diagnostic and repair issues of electro-automatic systems is based on the knowledge of the faults occurring in the systems in the process of their operation. The faults of the systems by the cause of occurrence can be divided into: faults resulting from wear and ageing of parts and components; faults resulting from construction errors and from low quality of manufacture; faults resulting from poor quality of servicing and repair; faults resulting from insufficient qualification of the operating personnel. Failures of systems in terms of their operability can be divided into: failures altering the characteristic of systems and deteriorating the quality of their operation; failures leading immediately to the shutdown of systems; failures directly affecting the quality of operation of systems, their characteristics and subsequently leading to their complete shutdown. System failures can be divided into: failures requiring repair of the system by replacement of the failed units and assemblies; failures requiring repairs without replacement of the units and assemblies; failures that were being repaired in the process of operation and maintenance of the systems. Before carrying out an emergency repair of the electro-automation, it is necessary to determine the nature of the fault and to specify as precisely as possible the location of the faulty element or component in the electrical, hydraulic or kinematic circuitry of the electro-automation. The purpose of the survey is to provide the operating personnel with a sequence of actions which result is in the detection of the fault or qualified personnel to be directed to the most likely faulty component. An algorithm for diagnostics of the "Complex 2E28M" tank weapon stabilization system in the "Target Designation" mode is presented. The algorithm is built by using the "Failure Tree" method to determine the state of complex technical systems. The advantages of the presented method of initial diagnostics are that it is possible for the crew with their own forces and means to detect small failures in the weapon stabilization system. On arrival of the specialised repair bodies, the crew directs them to the most likely cause of failure. In this way, all possible causes of failures in the system are tracked, providing instructions to the operating staff for elimination of the possible failures that have occurred. Using this method the time for product diagnostics is significantly reduced.